Análisis multitemporal de cambios de uso del suelo y coberturas, en la microcuenca las minas, corregimiento de La Laguna, municipio de Pasto, departamento de Nariño - Muñoz Guerrero, Diego; Rodríguez Montenegro, Mike; Romero Hernández, Mario (Revista de Ciencias Agrícolas, 2009)
A study about a multitemporal analysis of changes on soil use was carried out in "Las Minas" micro-basin which is located on the highest part in the "Alto Pedro" path (La Laguna), in the Southeast of the Municipality of Pasto. Its altitude ranges from 2.900 to 3.500 meters above sea level. The analysis evaluation was held over the past 19 years (from 1989 to 2008) through different cartographic tools such as the interpretation of photographs and the use of ArcView 3.2 program including 3dAnalysis, Spatial Analyst, Image Analyst, Image Warp y DNR Garmin. These images were taken from aerial photographs, satellite images, Landsat 10TM and IKONOS. It has been found a woodland loss of 58.51 hectares on account of a yearly deforestation of 3.08 hectares. The grass increase in the basin has been constant with an average of 2.54 hectares per year. The most considerable increase took place in 2008 because of the growing of a grass area of 141.64 hectares. As far as crops are concerned, the most considerable increase took place in 2008 since it went up to 28.13 hectares.